Relation between sarcopenia and hepatic encephalopathy in liver cirrhosis - a study in tertiary care hospital - Pathak, Rahul; Jha, Ashis Kumar; Jha, Anurag; Kafle, Brindeswari; Lamsal, Manoj (Bangladesh Journal of Medicine, 2024)
Introduction: Liver cirrhosis is a common medical problem associated with high morbidity and mortality. Consequences of cirrhosis leading to encephalopathy is a neuropsychiatric manifestation requiring hospital admission and poor prognosis. Similarly, sarcopenia in cirrhosis, resulting from multifactorial cause confers prognostic significance. The objective of this study is to find the relation between sarcopenia and hepatic encephalopathy. Methods: A retrospective observational study was conducted and data was taken from electronic medical records of patients admitted with hepatic encephalopathy in department of gastroenterology of Tribhuvan university Teaching hospital. A total of 96 cirrhotic patients were included during one and half year study duration. Sarcopenia was assessed using assessment tool like hand grip strength, chair stand test and CT measurement of either skeletal muscle area (SMA) or skeletal muscle index (SMI). Hepatic encephalopathy was graded according to West Haven criteria among admitted patients. Results: Among 96 patients with cirrhosis, 85 patients (88.5%) were found to have sarcopenia. Prevalence of sarcopenia was higher among female compared to male (97% vs 84%). Similarly, sarcopenia was found to be higher in patients with HE-2 and HE-3 compared to HE-1 ( 91% vs 93% vs 79% respectively). Conclusion: Sarcopenia is commonly associated with hepatic encephalopathy. Bangladesh J Medicine 2024; 35: 195-199